Investigating Diagnostic Problems of CIN1 and CIN2 Associated With High-risk HPV by Combining the Novel Molecular Biomarker PanHPVE4 With P16INK4a. (November 2015) - van Baars, Romy; Griffin, Heather; Wu, Zhonglin; Soneji, Yasmina J.; van de Sandt, Miekel M.; Arora, Rupali; van der Marel, Jacolien; ter Harmsel, Bram; Jach, Robert; Okon, Krzysztof; Huras, Hubert; Jenkins, David; et al.
Abstract : Grading cervical intraepithelial neoplasia (CIN) determines clinical management of women after abnormal cytology with potential for overdiagnosis and overtreatment. We studied a novel biomarker of human papillomavirus (HPV) life-cycle completion (panHPVE4), in combination with the minichromosome maintenance (MCM) protein cell-cycle marker and the p16 INK4a transformation marker, to improve CIN diagnosis and categorization. Scoring these biomarkers alongside CIN grading by 3 pathologists was performed on 114 cervical specimens with high-risk (HR) HPV. Interobserver agreement for histopathology was moderate (κ=0.43 for CIN1/negative, 0.54 for CIN2/⩽CIN1, and 0.36 for CIN3). Agreement was good or excellent for biomarker scoring (E4: κ=0.896; 95% confidence interval [CI]: 0.763-0.969; p16 INK4a : κ=0.798; 95% CI: 0.712-0.884; MCM: κ=0.894; 95% CI: NC (this quantity cannot be calculated). Biomarker expression was studied by immunofluorescence and immunohistochemistry and was correlated with 104 final CIN diagnoses after histologic review. All 25 histologically negative specimens were p16 INK4a and panHPVE4 negative, although 9 were MCM-positive. There were variable extents of p16 INK4a positivity in 11/11 CIN1 and extensive panHPVE4 staining in 9/11. Ten CIN2 lesions expressed panHPVE4 and p16 INK4a, and 13 CIN2 expressed only p16 INK4a . CIN3 showed extensive p16 INK4a positivity with no/minimal panHPVE4 staining. PanHPVE4, unlike MCM, distinguished CIN1 from negative. PanHPVE4 with p16 INK4a separated CIN2/3 showing only expression of p16 INK4a, indicating transforming HR-HPV E7 expression, from CIN1/2 showing completion of HR-HPV life cycle by E4 expression and variable p16 INK4a expression. PanHPVE4 and p16 INK4a staining are complementary markers that could provide simple, reliable support for diagnosing CIN. Their value in distinguishing CIN1/2 that supports HR-HPV life-cycle completion (and which might ultimately regress) from purely transforming CIN2/3 needing treatment warrants further research. Abstract : Supplemental Digital Content is available in the text.